Paternal unsafe home: Analysis of the political process of seizing and censorship in Iranian domestic violence cinema - Batyari, Atefeh (iQual. Revista de Género e Igualdad, 2025)
Iranian filmmakers always try to fulfill their mission to raising awareness by showing hidden and unpleasant social issues in the family and presenting a real picture of domestic violence, but the traditional view of the Iranian society towards the family as a sanctified taboo has been associated with the Islamicization policy of the Iran's regime. This petrified and biased view leads to the seize and censorship of films that break the taboo and show another side of family relationships. This article analyzes the view of patriarchy and cultural taboos of Iranian society in the banned films Friday Evening, The Paternal House and Girl's House ,by using the interpretivist criticism method. A critical look at Iran's politicized cinema can be effective to remove the barriers of raising awareness in the field of girls victims. The fusion of the Islamicization policies of the Iranian government with the society full of cultural taboos and sanctification of the family has caused films made in the field of domestic violence to face censorship and banning in order to break this sanctity. Separating cinema as a source of inspiration in the field of domestic violence prevention, from politics, will help the process of breaking unjustified cultural taboos and thus women's immunity from domestic violence.